Histopathological evaluation of endometrium and its clinical correlation in patients of abnormal uterine bleeding - Khatik, Neha; Tiwari, Arti; Yadav, Kalpana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Abnormal uterine bleeding (AUB) is a very common, challenging gynaecological problem in all age group women. Neoplastic lesions are responsible for very less number of cases but they should be diagnosed early. Endometrial biopsy is necessary for histopathological diagnosis of endometrial lesions and to rule out any malignancy. In present study, we evaluated histopathological pattern of endometrium and different clinical parameters in AUB patients. Methods: A retrospective observational study done in Obstetrics and Gynecology department of SSMC Rewa, Madhya Pradesh in 2 year from 1st October 2017 to 30th September 2019. AUB patients who fulfilled inclusion criteria were included in study. All data were collected from department records in predesigned proforma and statistically analyzed by statistical package for the Social sciences (SPSS) version 20. Results: Total 366 AUB patients were included in study; most frequent clinical presentation was HMB (56%). Mostly patient’s age ranged from 24-84 years, belonged to 41-50 years age group (44%), multiparous (78%), and premenopausal (53%). On histopathological evaluation of endometrium most commonly nonneoplastic lesions (75%) were seen, out of which proliferative phase endometrium was most frequent. Neoplastic lesions were seen in 25% cases. Out of which benign lesions were noted in 7%, premalignant in 17.3% and malignant in 1% (all in >45 year patients). Conclusions: Endometrial biopsy should be done in all AUB patients >45 years and in selected premenopausal in order to get early diagnosis, to rule out malignancy and to help in management. Endometrial biopsy should be considered as first diagnostic modality.